2012
DOI: 10.1167/iovs.11-7840
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosaKeratitis: Outcomes and Response to Corticosteroid Treatment

Abstract: Although P. aeruginosa corneal ulcers have a more severe presentation, they appear to respond better to treatment than other bacterial ulcers. The authors did not find a significant benefit with corticosteroid treatment, but they also did not find any increase in adverse events. (ClinicalTrials.gov number, NCT00324168.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 17 publications
1
62
0
2
Order By: Relevance
“…Clinical presentation of bacterial keratitis include acute pain, redness, photophobia and corneal ulceration [179]. Pseudomonas ulcers are more severe at presentation than other bacterial ulcers and are often difficult to treat, resulting in worse visual outcome than other bacterial ulcers [56,183].…”
Section: Bacterial Keratitismentioning
confidence: 99%
“…Clinical presentation of bacterial keratitis include acute pain, redness, photophobia and corneal ulceration [179]. Pseudomonas ulcers are more severe at presentation than other bacterial ulcers and are often difficult to treat, resulting in worse visual outcome than other bacterial ulcers [56,183].…”
Section: Bacterial Keratitismentioning
confidence: 99%
“…7 P. aeruginosa is the most common cause of Gramnegative bacterial keratitis 29,71 with a more severe clinical course than other bacterial pathogens if left untreated. 72 The healthy eye is generally protected against P. aeruginosa infection. Although cultured corneal epithelial cells are easily invaded and killed by most clinical and laboratory isolates of P. aeruginosa, 19,73 extremely large inoculates of invasive and cytotoxic P. aeruginosa onto intact mouse or rat corneas in vivo results in rapid bacterial clearance from the ocular surface without pathology.…”
Section: Pattern Recognition Mechanisms Activated By Microbial Pathogmentioning
confidence: 99%
“…Most ophthalmologists recommend starting anti-microbial empirically before culture results are available [37][38][39]. A study from Japan showed better results when anti-microbial agents were selected based on culture results, stressing the impor-tance of culture results [40].…”
Section: Management Of P Aeruginosa Keratitismentioning
confidence: 99%